Strength Analysis of Barge Structure on The Load Out Module Offshore Process Using Skidding Method - Palippui, Habibi; Sade , Juswan (Department of Ocean Engineering, Faculty of Engineering, Hasanuddin University, 2025)
The analysis of barge structural strength is crucial for ensuring safe and efficient load-out processes, particularly in evaluating the structure's capacity to withstand top-side loads during transfer from jetty to transportation barge. This study employs Finite Element Analysis to assess the barge structural integrity during the load-out process using the skidding method. Results demonstrate that the maximum von misses stress reaches 74.119 N/mm2 with a unity check (UC) of 0.422 < 1, while the maximum normal stress is 57,734 N/mm2 (UC 0.411 < 1), and shear stress remains minimal at 2.123 N/mm2 (UC 0.024 < 1). Peak stress occurs in load case 2, with the skid frame's ground bearing pressure at 6.83 Ton/m2 across an 85.05 m2 barge surface area. The findings validate that the skidding method is a viable approach for analyzing barge structural strength during load-out operations.